Imaging of the rabbit supraspinatus enthesis at 7 Tesla: a 4‐week time course after repair surgery and effect of channeling. Issue 2 (2nd February 2017) - Trudel, Guy; Melkus, Gerd; Cron, Greg O.; Louati, Hakim; Sheikh, Adnan; Larson, Peder E.Z.; Schweitzer, Mark; Lapner, Peter; Uhthoff, Hans K.; Laneuville, Odette
Abstract : Purpose: To image the supraspinatus enthesis reformation of rabbit shoulders by magnetic resonance at 7 Tesla (T) using T2 mapping after surgical repair and to assess the effects of channeling aimed at enhancing enthesis reformation. Materials and Methods: In 112 rabbits, the distal supraspinatus (SSP) tendon was unilaterally detached and reattached after 1 week. At the first surgery, channeling was performed at the footprint in 64 rabbits. At the second surgery, the SSP tendon of all rabbits was re‐attached to the greater tuberosity. The shoulders were harvested at 0, 1, 2, or 4 weeks after the repair surgery and were imaged at 7T. Quantitative T2 mapping was performed using multi slice two‐dimensional multi‐echo spin‐echo sequence with fat saturation. Enthesis regions of interests were drawn on three slices at the footprint to measure T2 relaxation times. Results: Tendon repair (F(2, 218) = 44; P < 2.2e‐16) and postoperative duration (F(3, 218) = 4.8; P = 0.006) both affected significantly the T2 values while channeling had no significant effect. For the time effect, the only pair with a statistical difference was the 0‐week and 4‐week for the channeling groups ( P = 0.023). Conclusion: Enthesis reformation early after surgical repair of the SSP distal tendon was characterized by increasing T2 values. Level of Evidence : 2 Technical Efficacy : Stage 1 J. MAGN. RESON. IMAGING 2017;46:461–467